Theoretical model for the relationship between the number of tackles a player engages in, tackle injury risk and performance in rugby union - Hendricks, S.; Micheal, L. (British Journal of Sports Medicine, 2014)
Background: The tackle in rugby union is a physical contest between opposing players contending for territory and ball possession. During an 80-minute rugby match, a player will physically engage in the tackle contest between 10 to 35 times. For a player to repeatedly engage safely and effectively in the tackle, a high level of skill and physical tolerance is required. Objective: Understanding the physical demands of a tackle is necessary for the design and development of proper training drills, equipment, planning and management of training, recovery between training sessions and matches, minimising the risk of injury., and to replicate the event in the laboratory for research. Design: Theoretical model.Setting Worldwide rugby playing population. Participants: All levels of play. Risk factor assessment: Magnitude of impact (energy load), number of tackles (during a match or over a season), muscle damage (micro trauma).Main outcome measurements Tackle injury risk and tackle performance. Results: It is theorised that players have a capacity to endure repeated high energy impact tackle situations. However, there is an upper limit, beyond which, the risk of injury is substantially increased, and tackle performance is noticeably decreased. This upper limit is reached either through one or two very high-energy impact contact situations or, accumulates over a match or season. Effective tackle skill training, proper physical conditioning, strength, power, equipment and attitude/motivation can offset the upper limit. Conclusions: Building on previous work in conjunction with the findings of Hendricks et al, a theoretical model for the relationship between the number of tackles a player engages in (acute or chronic fatigue), magnitude of impact (energy load), markers of muscle damage (micro trauma) and how this relationship interacts with tackle injury risk (tolerance overload or reduction) and tackle performance is proposed.